PENERAPAN PEMBELAJARAN BAHASA INGGRIS DENGAN METODE PEMBERIAN TUGAS UNTUK MENINGKATKAN HASIL BELAJAR SISWA 1 KELAS X SMAN 02 RAMBAH HILIR - ., Eripuddin (Edu Research, 2016)
This research aims to enhance the activity and results of learning English through the method of administration tasks for Class X SMAN Rambah Hilir Rokan Hulu. This type of research is a classroom action research investigators. The model used in this study is a model cycle. The strategy used in this study isÂ  classroom action research strategy with measures to hold action planning, observation or observation, carry out analysis and reflection. Data collection techniques used to obtain data inthis study, among other tests, as well as direct observation. The results showed that activity and increased student learning outcomes, in the first cycle obtained an average of learning outcomes, namely 76%. In Cycle II obtained an average value ofvalues of learning outcomes, namely 89%. From the results of these studies concluded that learning by using the method of administration tasks can increase the activity of students in learning English, and learning outcomes in students of Class X SMAN 02 Rambah Hilir to provide reinforcement and allow more students to participate in learning.